2023
DOI: 10.1002/pri.2054
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation for fatigue in neurological conditions: A systematic scoping review

Akhila Jagadish,
Apoorva M. Shankaranarayana,
Manikandan Natarajan
et al.

Abstract: Background and PurposeFatigue following neurological conditions negatively impacts daily activities, reducing overall quality of life. Transcranial direct current stimulation (tDCS) for fatigue management is still underexplored. This scoping review explores its use in managing fatigue among various neurological conditions.MethodsA thorough literature search was carried out using PubMed, Scopus, CINAHL, Web of Science, Embase, ProQuest, and the Cochrane Library. Google Scholar and clinicaltrials.gov were manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…Pro-cognitive effects were also shown in neurological disorders such as Parkinson's disease and stroke [52,53] and major neurodevelopmental disorders such as ADHD and autism [54][55][56]. It has been also effectively used for improving fatigue and quality of life [57,58]. The rationale behind the use of prefrontal tDCS for enhancing cognition mostly comes from the involvement of different regions of the prefrontal cortex in various aspects of cognitive functions [59][60][61] which seems to be at least partially applicable for MS.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-cognitive effects were also shown in neurological disorders such as Parkinson's disease and stroke [52,53] and major neurodevelopmental disorders such as ADHD and autism [54][55][56]. It has been also effectively used for improving fatigue and quality of life [57,58]. The rationale behind the use of prefrontal tDCS for enhancing cognition mostly comes from the involvement of different regions of the prefrontal cortex in various aspects of cognitive functions [59][60][61] which seems to be at least partially applicable for MS.…”
Section: Discussionmentioning
confidence: 99%
“…The above stimulation site and parameters were chosen based on the following rationale. First, association observed between increased fatigue scores and decreased functional connectivity of supplementary and primary motor areas ( 42 ). In addition, stimulation of motor cortex has been shown to improve fatigue in stroke patients and healthy individuals ( 31 , 71 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, stimulation of motor cortex has been shown to improve fatigue in stroke patients and healthy individuals ( 31 , 71 ). Second, the duration of stimulation per session was 20 min in all five published studies of tDCS on PSF ( 42 ). Third, consecutive sessions of tDCS has been employed were employed in previous studies of tDCS on PSF ( 32 , 34 , 71 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In stroke, tDCS has been explored for the recovery of motor [17] and language functions [18] but there are only limited studies focusing on reducing PSF [19][20][21] . Furthermore, the distinct cortical regions targeted in these studies exhibit considerable diversity [22] . The outcomes of these studies have demonstrated varying results, underscoring the need for additional exploration.…”
Section: Introductionmentioning
confidence: 99%